Building electromagnetic shielding characterisation using multicopter - Pienaar, H.; Otto, A.; Van Der Merwe, P.; Davidson, David; Reader, H. (2016)
© 2016 IEEE. We propose a multicopter scheme to characterize the shielding effectiveness of South Africa's Karoo Array Processing Building. The use of an autonomous multicopter with calibrated receiver and onboard antenna patterns is compared to conventional ground-based metrology. Measurement time and resolution are improved significantly. Our technique has been used during the evaluation of electromagnetic shielding policies during and after construction.